Effect of attenueted parapoxvirus ovis on levels of some serum cytokines and antibody response in sheep - Kamil Atlı; Atilla Şimşek (Eurasian Journal of Veterinary Sciences)
Aim: Parapoxvirus ovis (ORFV) infection is one of important contagious viral diseases of small ruminants. The aim of this study was to determine the concentration of cytokine and neutralizing antibody in blood serum of sheep that were carried out attenuated orf virus vaccine strain. Materials and Methods: In this study, 10 male Akkaraman sheep which are 6-8 months of age and tested negative for antibodies against ORFV were used. Scarification was applied with 0.5 ml of attenuated ORFV to each animal. Serum samples were obtained from vena jugularis at 0. hour (control) before the inoculation and at the following 6., 12., 24., 48., 72., 96., 120. hours, 7., 14., 21., 30., 60., 90., 120., 150. and 180. days. Neutralizing antibody presence was investigated in obtained serums. In addition, levels of IL-1?, IL-12, IFN-γ, TNF-α from proinflammatory cytokines (Th1) and IL-4 and IL-10 from antiinflammatory cytokines (Th2) were determined by ELISA. Results: ORFV caused fluctiations but no statistically significant change in levels of IL-1β, IL-12, IFNγ, TNF-α and IL-10 were detected compared to control sera (p>0,05), and significant increase in IL-4 level was detected in the 30th day (p<0,05). As a result of the study, attenuated live ORFV administration and have no effect on levels of some serum cytokine except IL-4 and neutralizing antibodies. Conclusion: It was concluded that the vaccines against ORFV infection considered to be used in the future should be applied after the effects on the immune system have been clearly demonstrated.